The Benefit of the Gift Social Organization and Expanding Networks of Interaction in the Western Great Lakes Archaic - Hill, Mark Andrew (International Monographs in Prehistory: Archaeological Series, 2012)
Archaeological data from the Late Archaic (4000-2000 years ago) in the Western Great Lakes are analyzed to understand the production and movement of copper and lithic exchange materials. Also considered in this volume are access to and benefits from exchange networks, as well as social changes accompanying the development of extensive, continental scale, exchange systems of interaction in this period